2010
DOI: 10.1063/1.3459961
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid conjugated polymer solar cells using patterned GaAs nanopillars

Abstract: In this work, we study hybrid solar cells based on poly(3-hexylthiophene)-coated GaAs nanopillars grown on a patterned GaAs substrate using selective-area metal organic chemical vapor deposition. The hybrid solar cells show extremely low leakage currents (I≅45 nA @−1V) under dark conditions and an open circuit voltage, short circuit current density, and fill factor of 0.2 V, 8.7 mA/cm2, and 32%, respectively, giving a power conversion efficiency of η=0.6% under AM 1.5 G illumination. Surface passivation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 15 publications
(14 reference statements)
1
41
0
Order By: Relevance
“…This is because the density of surface states at the polymer/GaAs interface has a particularly large effect on the J sc , as the highest charge carrier generation region is at this interface. Therefore, reducing the surface recombination at the polymer/ GaAs interface would increase the J sc [14]. In fact, similar behavior has been observed in Si based hybrid Schottky junction type solar cells [17].…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…This is because the density of surface states at the polymer/GaAs interface has a particularly large effect on the J sc , as the highest charge carrier generation region is at this interface. Therefore, reducing the surface recombination at the polymer/ GaAs interface would increase the J sc [14]. In fact, similar behavior has been observed in Si based hybrid Schottky junction type solar cells [17].…”
Section: Resultsmentioning
confidence: 66%
“…It has been found that surface passivation can largely reduce the density of surface states and lower surface non-radiative recombination [14]. The lower density of surface states would also reduce the Fermi level pining effect, to enhance the built-in electrical field in the solar cell, leading to higher open circuit voltage [9].…”
Section: Resultsmentioning
confidence: 99%
“…Surface passivation aims to rebond these dangling bonds with certain passivating agents while maintaining charge neutrality after the passivation [45]. For instance, one recent study of hybrid solar cells based on poly (3-hexylthiophene) and GaAs nanopillars [40] shows that the surface passivation is crucial to alleviate the surface states on the nanopillar facets, leading to a much enhanced efficiency. Nonetheless, only simple inorganic molecules were adopted (e.g.…”
Section: Surface Passivationmentioning
confidence: 99%
“…nanowires). For instance, hybrid solar cells can be created by coating poly (3-hexylthiophene) (P3HT) on GaAs nanowires by carefully tuning the spincoating conditions [40]. A standard fabrication process is presented in Fig.…”
Section: Controlled Spin-coatingmentioning
confidence: 99%
“…1 Many SAE-NW-based devices have recently been demonstrated including photonic crystal cavities, 2 Fabry-Perot resonators, 3 lasers, 4 photo-detectors, 5,6 and various solar cell designs. [7][8][9] In addition, research demonstrating the direct growth of compound semiconductor SAE-NWs on silicon has shown a pathway to direct integration of photonic devices onto CMOS chips, possibly providing a much sought after solution to a long standing technical challenge. 10,11 A major advantage of the SAE technique over other growth methods is the inherent lithographic control of the location and size of the wires; making it possible to design site-controlled, arraybased devices.…”
mentioning
confidence: 99%